Physico-chemical properties of mixed jam from pineapple and sweet gourd - Ferdous, MJ; Alim, Md Abdul (Journal of the Bangladesh Agricultural University, 2018)
This study investigated the preparation of mixed jam from sweet gourd and pineapple. The proximate compositions of sweet gourd pulp were: moisture content 90.3%, ash 0.33%, sugar 3.24% and ascorbic acid 2.97 mg/100g. Pineapple pulp contained 74.6%moisture, 0.3%ash, 9.95% sugar and 78.79 mg/100 gascorbic acid. The keeping quality and shelf life of the prepared mixed jam were studied. For the case of mixed jam, the highest sugar content (62.54%) was in sample with 60% pineapple and 40% sweet gourd. Organoleptic test showed that overall acceptability of 60% pineapple +40% sweet gourds was better than that of other mixed jam. The highest score (8.0) was found from the sample with 60% pineapple + 40% sweet gourd, and the lowest score (6.0) was from the sample with 50% pineapple + 50% sweet gourd. During storage period, TSS, reducing sugar, non-reducing sugar and pH decreased for all cases. Fading of color was observed at 90 days of storage for some samples. J. Bangladesh Agril. Univ. 16(2): 309-314, August 2018